PEMETAAN SISTEM INFORMASI BERDASARKAN SUMBER DAN KEBUTUHAN UNTUK PEMBUATAN KEPUTUSAN DI DINAS KESEHATAN - Al Wafi Rahmaputri Ardianingrum; Lutfan Lazuardi (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2021)
Background: Ngawi Regent Regulation Number 39 of 2008 concerning Duties, Functions, and Authorities of the Ngawi Regency Office, the function is to formulate technical policies in the health sector. According to Government Regulation Number 36 of 2014 concerning Health Information Systems, it is written that every health facility is required to record and report. Therefore, research required mapping information systems based on sources and availability for decision making at the Ngawi District Health Office. Objective: To identify the information systems and decisions made by the Ngawi District Health Office. Methods: This research is a type of qualitative descriptive research that uses a case study design. The research subjects are stakeholders who understand and are responsible for health programs and policymakers within the Ngawi District Health Office. Data analysis used thematic analysis. Results: The Ngawi District Health Office uses 31 active applications for daily activities. The infrastructure used to support minimal activities is laptops, applications, and internet networks. Data collection starts with the primary health care, health office, and health ministry. The decisions contained in the Ngawi District Health Office are programmed and non-programmed decisions. In 2020, non-programmed decisions were decisions related to the Covid-19 pandemic. Information system mapping has been carried out with an overview of the applications used by each sector in the health office and the data sources used. Conclusion: The Ngawi District Health Office has 31 active applications. The six applications have been integrated, 18 have not been integrated, and 12 applications can be integrated without having to enter the same data twice. There is no standard operating procedure in the public health department at the health office.